The Effect of Exchange Rate on Cross-Border Mergers and Acquisitions (CBMAs) Success: Evidence from ASEAN CBMA - Nurhazrina MAT RAHIM; Ruhani ALI; Ei Yet CHU (Communications of International Proceedings, 2020)
CBMA is one of the preferred external growth strategies by many firms worldwide. Similar trend is also observed for firms from ASEAN member countries. Nevertheless, it is reported that there is high rate of non-value creation involving CBMAs transactions due to higher risk as compared to domestic M&As. Exchange rate is one of the sources of risk related to CBMAs transaction.  This study aims at examining the role of exchange rate in ASEAN firms’ CBMA success. This is due to the active involvement of ASEAN firms in CBMA and high exchange rate volatility in ASEAN countries. This study used CBMA involving 348 ASEAN bidding firms and 246 ASEAN target firms from the year 2002 to 2013 from Thomson One Banker Database. The results from multiple regression analysis indicate that exchange rate strength is disadvantageous for ASEAN target firms as it would decrease the possibility of CBMA success. The results contradict to cost of capital view which argue that stronger bidder’s currency resulted high premium payment and increase the possibility of CBMA success. Hence ASEAN target firms should be more cautious in due diligence process prior to accepting CBMA offer from country with stronger currency.
Keywords: Cross-border mergers and acquisitions (CBMAs); Exchange rate; CBMA Success; ASEAN.